Campur Kode dan Alih Kode pada Mahasiswa S1 Sastra Jepang Angkatan 2017/2018 Universitas Ngudi Waluyo - Umi Handayani (Faculty of Economics, Law, and Humanities, 2019)
Code switching and code mixing is one phenomenon in social interaction. Thisphenomenon often arises in bilingual or people who speak more than two languages(multilingual). Japanese Literature Students of Universitas Ngudi Waluyo, 2017/2018 aspart of a multi-lingual society, also experienced events called code switching and codemixing. Mastery of Japanese is certainly inﬂuential on student interaction outside theclassroom. This research needs to be done to fnd out the events of code switchingand code mixing that occur. This research is based on the idea that the language usedby Japanese Literature students at Universitas Ngudi Waluyo in class of 2017/2018 ininteracting with each other outside the classroom also includes the Japanese languageas a second language, even the third language that students master. Besides that, it alsolooks at how the 2017/2018 Japanese literature students enter Japanese in interacting, asa choice of language that they think is appropriate.Keywords: code, code switching, code mixing